2008
DOI: 10.1128/aem.01099-08
|View full text |Cite
|
Sign up to set email alerts
|

An Amino Acid Substitution at Position 740 in σ 70 of Ralstonia solanacearum Strain OE1-1 Affects Its In Planta Growth

Abstract: Growth of Ralstonia solanacearum strain OE1-1 in roots after invasion is required for virulence. An Arg740Cys substitution in 70 of OE1-1 resulted in loss of in planta growth and virulence. The negative dominance of mutant 70 over the wild-type protein suggested that the amino acid substitution may affect the in planta growth of OE1-1, leading to a lack of virulence.Ralstonia solanacearum strain OE1-1 shows virulence on tobacco, as well as tomato and eggplant, plants (17). OE1-1 possesses hrp genes, similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Multiple alignments of the deduced amino acid sequences of LOV proteins from representative strains belonging to the four phylotypes including: Rpso GMI1000 (phylotype I) 23 , Rpso strain OE1-1 (phylotype I) 35 , Rpso FQY_4 (phylotype I) 36 , Rso K60 (phylotype IIA) 37 , Rso CFBP2957 (phylotype IIA) 38 , Rso IPO1609 (phylotype IIB) 38 , Rso UW551 (phylotype IIB) 38 , Rso Po82 (phylotype IIB) 39 , Rso UY331 (phylotype IIB) 40 , Rpso CMR15 (phylotype III) 38 , R. syzygii R24 (phylotype IV) 41 and R. syzygii PSI07 (phylotype IV) 38 revealed that the LOV protein is present in all Rso strains sequenced and possess highly conserved domains suggesting that light would play an important role in the Rso free lifestyle and during the plant-interaction (Supplementary material S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple alignments of the deduced amino acid sequences of LOV proteins from representative strains belonging to the four phylotypes including: Rpso GMI1000 (phylotype I) 23 , Rpso strain OE1-1 (phylotype I) 35 , Rpso FQY_4 (phylotype I) 36 , Rso K60 (phylotype IIA) 37 , Rso CFBP2957 (phylotype IIA) 38 , Rso IPO1609 (phylotype IIB) 38 , Rso UW551 (phylotype IIB) 38 , Rso Po82 (phylotype IIB) 39 , Rso UY331 (phylotype IIB) 40 , Rpso CMR15 (phylotype III) 38 , R. syzygii R24 (phylotype IV) 41 and R. syzygii PSI07 (phylotype IV) 38 revealed that the LOV protein is present in all Rso strains sequenced and possess highly conserved domains suggesting that light would play an important role in the Rso free lifestyle and during the plant-interaction (Supplementary material S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…1, Yamato Plastic Co. Ltd., Yamatotakada, Japan) with fivefold‐diluted Hoagland’s solution. At 10 days post‐inoculation, after sterilization of plant surfaces with 70% ethanol, the roots and stems of five tomato plants were cut into three pieces each using razor blades (Kanda et al ., ). The cut site of each piece (I, roots; II and III, stems; Fig. )…”
Section: Methodsmentioning
confidence: 97%
“…The colonies were counted after 2 days of incubation at 30 8C. A plate-printing assay was performed as follows (Kanda et al, 2008). At 10 days post-inoculation by root dipping, the roots and stems of five tomato plants were cut into three pieces each using razor blades.…”
Section: Bacterial Populations and Behaviour In Tomato Plantsmentioning
confidence: 99%
“…Ralstonia solanacearum is a soil-borne bacterium that normally invades plant roots from the soil through wounds or natural openings where secondary roots emerge (Araud-Razou et al, 1998), colonizes intercellular spaces of the root cortex and vascular parenchyma, and eventually enters xylem vessels and spreads up into the stems and leaves through the xylem (Hikichi, 2016;Hikichi et al, 2017;Vasse et al, 1995). This colonization in intercellular spaces is required for the virulence of the wild-type strain of R. solanacearum (OE1-1) (Hikichi, 2016;Hikichi et al, 1999Hikichi et al, , 2017Kanda et al, 2003Kanda et al, , 2008Mori et al, 2016;Shinohara et al, 2005). Following the invasion of the intercellular spaces of tomato plants, strain OE1-1 forms mushroom-shaped biofilms (mushroom-type biofilms, mBFs) on the surfaces of tomato cells adjacent to intercellular spaces, leading to the colonization of intercellular spaces (Hikichi, 2016;Hikichi et al, 2017;Mori et al, 2016).…”
Section: Introductionmentioning
confidence: 99%